Only Tumors Angiographically Identified as Hypervascular Exhibit Lower Intraoperative Blood Loss Upon Selective Preoperative Embolization of Spinal Metastases: Systematic Review and Meta-Analysis - Gong, Yining; Wang, Changming; Liu, Hua; Liu, Xiaoguang; Jiang, Liang (Frontiers in Oncology, 2021)
Background The role of preoperative embolization (PE) in reducing intraoperative blood loss (IBL) during surgical treatment of spinal metastases remains controversial. Methods A systematic search was conducted for retrospective studies and randomized controlled trials (RCTs) comparing the IBL between an embolization group (EG) and non-embolization group (NEG) for spinal metastases. IBL data of both groups were synthesized and analyzed for all tumor types, hypervascular tumor types, and non-hypervascular tumor types. Results In total, 839 patients in 11 studies (one RCT and 10 retrospective studies) were included in the analysis. For all tumor types, the average IBL did not differ significantly between the EG and NEG in the RCT (P = 0.270), and there was no significant difference between the two groups in the retrospective studies (P = 0.05, standardized mean difference [SMD] = −0.51, 95% confidence interval [CI]: −1.03 to 0.00). For hypervascular tumors determined as such by consensus (n = 542), there was no significant difference between the two groups (P = 0.52, SMD = −0.25, 95% CI: −1.01 to 0.52). For those determined as such using angiographic evidence, the IBL was significantly lower in the EG than in the NEG group, in the RCT (P = 0.041) and in the retrospective studies (P = 0.004, SMD = −0.93, 95% CI: −1.55 to −.30). For IBL of non-hypervascular tumor types, both the retrospective study (P = 0.215) and RCT (P = 0.947) demonstrated no statistically significant differences in IBL between the groups. Conclusions Only tumors angiographically identified as hypervascular exhibited lower IBL upon PE in this study. Further exploration of non-invasive methods to identify the vascularity of tumors is warranted.